A Stretch of Negatively Charged Amino Acids of Linker for Activation of T-Cell Adaptor Has a Dual Role in T-Cell Antigen Receptor Intracellular Signaling - Arbulo-Echevarria, Mikel M.; Narbona-Sánchez, Isaac; Fernandez-Ponce, Cecilia M.; Vico-Barranco, Inmaculada; Rueda-Ygueravide, Mª Dolores; Dustin, Michael L.; Miazek, Arkadiusz; Duran-Ruiz, Mª Carmen; García-Cózar, Francisco; Aguado, Enrique (Frontiers in Immunology, 2018)
The adaptor protein Linker for Activation of T cells (LAT) has an essential role transducing activatory intracellular signals coming from the TCR/CD3 complex. Previous reports have shown that upon T cell activation LAT interacts with the tyrosine kinase Lck, leading to the inhibition of its kinase activity. LAT-Lck interaction seemed to depend on a stretch of negatively charged amino acids in LAT. Here we have substituted this segment of LAT between amino acids 113 and 126 with a non-charged segment, and expressed the mutant LAT (LAT-NIL) in J.CaM2 cells in order to analyze TCR signaling. Substitution of this segment in LAT prevented the activation induced interaction with Lck. Moreover, cells expressing this mutant form of LAT showed a statistically significant increase of proximal intracellular signals such as phosphorylation of LAT in tyrosine residues 171 and 191, and also enhanced ZAP70 phosphorylation approaching borderline statistical significance (p=0.051). Nevertheless, downstream signals such as Ca2+ influx or MAPK pathways were partially inhibited. Overall, our data reveal that LAT-Lck interaction constitutes a key element regulating proximal intracellular signals coming from the TCR/CD3 complex.